Migraine and School Performance in Preadolescent Children - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Researchers at the Glia Institute, Brazil; Albert Einstein College of Medicine, NY; and other centers conducted a population-based study of school performance in children in Brazil with migraine.